HAK DAN PERLINDUNGAN ANAK DALAM PENDIDIKAN ISLAM - Muhammad Syafril Sunusi; Saprin, Saprin; Syarifuddin Ondeng (CV. ADIBA AISHA AMIRA, 2024)
This article aims to provide an understanding of children's rights and protection from an Islamic perspective. Specifically about how to fulfill children's needs. Welfare is a condition where all a person's life needs can be fulfilled and can achieve satisfaction. Children are the ones whose welfare must be taken into account, whether it is physical welfare, inner welfare, or social welfare because children are individuals who will carry on their dreams. -the ideals of the nation and becoming the next generation of a country. Currently, the condition of children in Indonesia still needs to be addressed by the government and other parties because their welfare is problematic. There are many things that cause children's needs and rights to not be met, Fulfilling the rights of children who are deprived of them because they have to work and the influence of the psychosocial conditions of children when they work will affect the child's growth and development process. Islam views children as expensive gifts with sacred status. This expensive gift is a trust that must be guarded and protected by parents in particular, because children are assets of parents and assets of the nation. Islam has paid great attention to the protection of children. Protection in Islam includes physical, psychological, intellectual, moral, economic and others. This is explained in the form of fulfilling all their rights, guaranteeing their food and clothing needs, maintaining their good name and dignity, maintaining their health, choosing good friends to associate with, avoiding violence, and so on.